Peace as the Basis of Human Civilization: Philosophical and Socio-Cultural Views - A. A. Kovalev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The goal — the study of peace and peaceful existence as the basis of the entire human civilization — has been achieved by solving of the following tasks: 1) philosophical and linguistic analysis of the concepts of «peace» and «peaceful existence»; 2) consideration of the problem of peaceful existence in a logical-historical aspect; 3) the study of the praxeological aspect of the problem, that is, specific ways to achieve peace; 4) consideration of the essence and foundations of the social world; 5) highlighting the role of religions and religious denominations to ensure a peaceful existence. Research methods include methods of historical and philosophical, cultural and linguistic analysis, comparative approach. Results. The main aspects of peaceful existence as a basic concept of the whole human history and civilization have been considered. Peace and war as two dialectical foundations of human existence are closely interconnected throughout world history. This proves both the conducted linguistic analysis and the logical-historical approach to the problem of peaceful existence. The state of the peace was not always recognized as indispensable for individual and social being. Following Heraclitus, philosophers often had recognized the benevolent nature of war as a factor that binds states and nations together. But in the twentieth century, the war acquired such qualitative characteristics that any military confrontation can lead to a nuclear apocalypse, although even today many advanced technologies appear precisely in the military industry. In the era of civilizational confrontation caused by globalization processes, the achievement and preservation of universal peace has become a vital task for all mankind. Findings. The notions of a peaceful existence have evolved from thinking about the artificiality of the world and the naturalness of hostility and war for humanity and the individual to the axiomatic concepts that extol world peace on the planet as the only means to avoid nuclear apocalypse. Globalization can contribute to the awareness of the fragility of the entire human civilization and the uniqueness of the sociocultural formations that make it up. In order to achieve peace on the planet, it is necessary to abandon attempts to unify it by force. The entire wealth of human culture cannot be simplified and unified within the framework of a single geopolitical, economic and cultural paradigm. Aggressive attempts of such a kind can lead to the complete destruction of mankind.